Designing a prototype of wireless internet hotspot at Kolej Teratai 3 in UiTM Shah Alam / Nurhayati Othman - Othman, Nurhayati (2005)
Wireless hotspot is a public area where people can surf Intemet without using wire or cable. Kolej Teratai was chosen because it has potential to be one of the wireless hitemet hotspots places available in UiTM Shah Alam. The objectives of this research are to design a network diagram for implementation of wireless Intemet hotspot in Kolej Teratai 3 and to test the signal strength of wireless Intemet service at the college so that suitable locations of Access Point can be determined. For this project the scope was limited for Kolej Teratai 3 only, and at least three levels in the building can get the internet connection. To accomplish the objectives, research methodologies such as information gathering, information analysis, designing them network diagram, testing the signal and make documentation was followed. From the test that had been done, an Access Point can cover two levels in the same building and additional devices such as antenna will be needed to expand the signal coverage